Application of acoustic models for polydisperse emulsion characterization using ultrasonic spectroscopy in the long wavelength regime - Silva, Carlos A. M.; Saraiva, Samuel; Bonetti, Darlan; Higuti, Ricardo T. [UNESP]; Cunha, Rosiane L.; Pereira, Luiz O.; Silva, Flavio; Fileti, Ana M. F. (Elsevier B.V., 2020)
Ultrasonic spectroscopy is a technique that often has been used for measuring the particle size distribution in suspensions and emulsions. The ability to analyze concentrated heterogeneous systems and optically opaque samples, without the need for dilution, is the major advantage over alternative technologies, such as light scattering method. Several physical models used to interpret the measured attenuation spectra have been applied considering monodisperse particles. However, the polydisperse particle distributions are found in many practical applications, for example, in crude oil emulsions during droplet coalescence or flocculation. The polydispersity effects are usually important and need to be incorporated into theoretical predictions. For this work, acoustic spectroscopy within the frequency range 6-14 MHz was used to measure the droplet size distribution of water-in-sunflower oil emulsions for a volume fraction range from 10 to 50 % and considering monomodal size distribution. The results obtained from experimental attenuation spectra have been compared with the predictions of acoustic models from simple and multiple scattering, extended multiple scattering, and other simpler models of propagation usually applied to the long wavelength regime. The droplet size distributions from theoretical and experimental attenuation spectra were calculated with a deconvolution algorithm. The size distribution results obtained by ultrasonic spectroscopy showed good agreement with those obtained by laser diffraction analysis. The findings indicate that the methodology employed in this study is suitable for polydisperse particle size characterization for moderate concentrations up to 20 %.
Keywords: Attenuation spectra; Acoustic models; Droplet characterizations; Emulsion; Ultrasonic spectroscopy